Statistical Analysis of Some Socioeconomic Factors Affecting Age at Marriage among Males in Kogi State, Nigeria - Awe, Olushina O.; Adarabioyo, M. I.; Lawal, F. K.; Damola, Ayemidotun (2014)
This study is aimed at investigating the relationship between age at marriage and educational attainment, religion and cultural background among males in some parts of South -Western Nigeria. A saturated one-way and two-way model was proposed for the study. Level of educational attainment and religion was established to have significant relationship with age at marriage while senatorial differences do not have any statistical significant relationship with age at marriage in the area surveyed.